2015
DOI: 10.1111/imm.12420
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of granzyme B‐expressing CD8 T cells during primary and secondary immune responses to Listeria monocytogenes

Abstract: SummaryCD8 T cells contribute to long-term protection against Listeria monocytogenes infection by differentiating into memory T cells. These rapidly respond to antigen or inflammation upon secondary infection. In this study we used CD8 T cells from OT1 mice and CD4 T cells from OT2 mice expressing a fluorescent chimeric granzyme (GZMB-Tom) protein to monitor the primary response to infection with ovalbumin-expressing L. monocytogenes (Lm-OVA). We show that, unlike poorly responding CD4 T cells, CD8 T cells rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(97 reference statements)
1
10
0
Order By: Relevance
“…3b). Similar proportions of CD4 + cells are reported in mouse lymph node (Mouchacca et al, 2015). The proportion of cellular expression of CD4 in primary and secondary lymphoid organs is similar to human and mouse (Lagresle-Peyrou et al, 2006).…”
Section: Hybridoma Generationsupporting
confidence: 76%
“…3b). Similar proportions of CD4 + cells are reported in mouse lymph node (Mouchacca et al, 2015). The proportion of cellular expression of CD4 in primary and secondary lymphoid organs is similar to human and mouse (Lagresle-Peyrou et al, 2006).…”
Section: Hybridoma Generationsupporting
confidence: 76%
“…In addition to the Fas/FasL-pathway, T-cell cytotoxicity involves exocytosis of granules containing perforin and granzymes [ 38 ]. Previous studies showed lowered [ 56 ] or absent [ 30 ] intrathecal expression of perforin and grB by CD8 + T cells in non-inflammatory CNS conditions, suggesting a functionally repressed phenotype of CNS surveilling T cells.…”
Section: Resultsmentioning
confidence: 99%
“…4 c). Collectively, the data indicate that CD8 + T cells in WML of MS patients analyzed express a cytotoxic phenotype indicative for T cells recognizing their cognate antigen in situ [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations